Uso de scanner 3D para o controle dimensional de peças em produção: análise da implementação e seus impactos - Lima, Renan Duarte de (2023)
The simultaneous increasing of industrial automation and products requirements for specifications and tolerances expects higher quality assurance, productivity and safety, and new measurement methods emerged to supply these needs: among them the dimensional measurement using 3D scanner has arrived. The researches developed so far showed the technical benefits compared to different measurement methods available in the market but did not explore the potential social, measurement accuracy, production capacity and economic benefits the implementation of this kind of technology can bring to companies. This research shows a case study in an aftertreatment system manufacturer which compares this technology (3D scanner) related to a conventional measurement method (three- dimensional measurement arm) The study objective was identifying the potential social benefits, measurement accuracy, production capacity and economic throughout the measurement usage through 3D scanner in production environment. The research results showed that despite of return over investment being unattractive, it eliminated the high operator’s ergonomics risk utilizing the measurement arm. Besides that, the measurement method accuracy related to the critical product features is substantially higher: three-dimensional measurement arm showed 24.01% as repeatability and reproducibility rate in its worst feature measured (just conditionally capable) while measurement system with robot plus 3D scanner showed only 4.26% (totally capable). Ultimately, it is possible to realize in terms of new products and businesses searching that scanner 3D eliminates a potential constraint for measurement station capacity (approximately 20,700 parts/year for measurement arm against 69,100 parts/year for 3D scanner). This study looked for stimulate companies to evaluate alternatives related to potential earnings from 4.0 Industry used for quality control of processes.